Răspuns :
a) −5x+2=−4x+1−5x+2+4x=−4x+1+4x
−x+2=1
−x+2−2=1−2−x=−1
[tex] \frac{-x}{-1} = \frac{-1}{-1} [/tex]
x=1
b)3x−9+x=2x−27
4x−9=2x−27
4x−9−2x=2x−27−2x2x−9=−272x−9+9=−27+92x=−18
[tex] \frac{2x}{2} = \frac{-18}{2} [/tex]
x=−9
c)5x+13−2x=9x+22−5x
3x+13=4x+22
3x+13−4x=4x+22−4x−x+13=22
−x+13−13=22−13−x=9
[tex] \frac{-x}{-1}= \frac{9}{-1} [/tex]
x=−9
−x+2=1
−x+2−2=1−2−x=−1
[tex] \frac{-x}{-1} = \frac{-1}{-1} [/tex]
x=1
b)3x−9+x=2x−27
4x−9=2x−27
4x−9−2x=2x−27−2x2x−9=−272x−9+9=−27+92x=−18
[tex] \frac{2x}{2} = \frac{-18}{2} [/tex]
x=−9
c)5x+13−2x=9x+22−5x
3x+13=4x+22
3x+13−4x=4x+22−4x−x+13=22
−x+13−13=22−13−x=9
[tex] \frac{-x}{-1}= \frac{9}{-1} [/tex]
x=−9
a)-5x+2=-4x+1
-5x+4x=1-2
-x=1
b) 3x-9+x=2x-27
4x-9=2x-27
4x-2x=-27+9
2x=-18
x=-18:2
x=-9
c) 5x+13-2x=9x+22-5x
3x+13=4x+22
3x-4x=22-13
x=-9
-5x+4x=1-2
-x=1
b) 3x-9+x=2x-27
4x-9=2x-27
4x-2x=-27+9
2x=-18
x=-18:2
x=-9
c) 5x+13-2x=9x+22-5x
3x+13=4x+22
3x-4x=22-13
x=-9